Optimisation of protoplast isolation protocols using in vitro leaves of Dendrobium crumenatum (pigeon orchid) - Tee, Chong Siang; Lee, Pui Sinn; Ling, Anna Pick Kiong; Mahmood, Maziah (Academic Journals, 2010)
Protoplast isolation from in vitro leaves of Dendrobium crumenatum was carried out. Factors affecting protoplast isolation, sorbitol concentration, enzyme combinations and concentration and incubation time for isolation were studied. Results obtained showed that 0.5 M sorbitol was the most effective concentration to isolate the protoplast (25.62×104 protoplasts/g FW). High yield of protoplasts, 20.40×104 protoplasts/ g FW, could also be obtained by using combination of cellulase and pectinase instead of using the enzyme individually. In addition, efficacy of protoplast isolation was improved by 20.12×104 protoplasts/g FW, when 2% (w/v) cellulase and pectinase were used; while incubation for 4 h during the isolation process recorded highest protoplast yield, 28.66×104 protoplasts/gFW. Based on the results obtained, we suggest that protoplasts isolation of D. crumenatum from in vitro leaves could be achieved using 0.5 M sorbitol with combination of 2% (w/v) cellulase and pectinase for both enzymes and 4 h incubation time.